Effects of Subchronic Treatment of Parathion on Immune Potential Marker Enzymes of Rats - SUZEK, HUSEYIN (Asian Journal of Chemistry, 2010)
The effects of methyl parathion in sublethal concentration on immune potential enzymes [adenosine deaminase and myeloperoxidase] of rats was investigated under laboratory conditions. Methyl parathion (5 and 10 ppm) was administered orally to 6 female rats ad libitum during the tests for 4 weeks consecutively. Various tissues adenosine deaminase and myeloperoxidase activities of rat were determined after treatment. The results showed that methyl parathion resulted different effects on the enzymes activities compared with control rats. Methyl parathion treatments increased significantly adenosine deaminase and myeloperoxidase activity except for liver myeloperoxidase activity with both two dosages treatment. The observations presented led us to conclude that methyl parathion produced substantial systemic organ toxicity in rats during the period of a 28 d subchronic exposure.